2021
DOI: 10.28976/1984-2686rbpec2021u13171338
|View full text |Cite
|
Sign up to set email alerts
|

A Experimentação na Educação em Química Verde: uma Análise de Propostas Didáticas Desenvolvidas por Licenciandos em Química de uma IES Federal Paulista

Abstract: Este trabalho busca analisar a inserção dos Princípios da Educação em Química Verde (EQV) nas propostas experimentais desenvolvidas pelos estudantes na disciplina de Experimentação na Educação Química do curso de Licenciatura em Química de uma Instituição de Ensino Superior (IES) federal localizada no estado de São Paulo. As propostas desenhadas pelos estudantes foram analisadas de acordo com os níveis de grau verde correspondentes aos Princípios da EQV. De acordo com as análises, verificou-se que as propostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…We wish to highlight that energy is the only crosscutting concept that is at the same time a core disciplinary content for GC. The results of this study support the importance of the concept of energy, not only as a crosscutting concept but as a key idea connecting the model of educational reconstruction of GC and the principles of GC for education (Saqueto, 2015;Zuin et al, 2019;Andrade and Zuin, 2021).…”
Section: Interdisciplinary Dimension Of the Curricular Content For Gcsesupporting
confidence: 68%
See 1 more Smart Citation
“…We wish to highlight that energy is the only crosscutting concept that is at the same time a core disciplinary content for GC. The results of this study support the importance of the concept of energy, not only as a crosscutting concept but as a key idea connecting the model of educational reconstruction of GC and the principles of GC for education (Saqueto, 2015;Zuin et al, 2019;Andrade and Zuin, 2021).…”
Section: Interdisciplinary Dimension Of the Curricular Content For Gcsesupporting
confidence: 68%
“…Similarly, principles linking GC to engineering have been developed in the so-called green engineering, with publications such as The 24 Principles of Green Engineering and Green Chemistry: Improvements Productively (Tang et al, 2008). Principles of GC education (GCE) have even been developed (Saqueto, 2015;Zuin et al, 2019;Andrade and Zuin, 2021), to promote the introduction of GC into chemistry education, offering a new framework for its development at the university level.…”
Section: Green Chemistrymentioning
confidence: 99%
“…Although the literature reports several metrics for evaluations of chemical processes in the laboratory, it is observed that there is still a need for metrics that integrate Green and Sustainable Chemistry with the pedagogical aspects necessary for a critical formation - mainly regarding fundamental theoretical aspects, such as the experiment approach, scientific literacy, and learning models in Education for Sustainable Development, which guide the development of greener experimental proposals in teacher training in chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…This may be designated as the critical level. According to Andrade and Zuin (2023) [18], there are three levels of scientific literacy for experimentation in Green and Sustainable Chemistry. By analyzing student experiments in a university chemistry course, these authors found that most aligned with conceptual literacy.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…According to the literature, authors have proposed models for the integration of Green Chemistry into chemistry curricula [17][18][19]. In Brazil, Sandri and Santi Filho (2019) [19] expanded upon the frameworks proposed by Burmeister, Rauch, and Eilks (2012) [20], classifying the contributions of teaching Green Chemistry in three models.…”
Section: Introductionmentioning
confidence: 99%